Housing Informalities Between Formal Designs and Informal Reality - Rim Mrani; Jérôme Chenal; Hassan Radoine; Hassan Yakubu (Architecture)
Housing informality (HI), and particularly unauthorized modifications, are a widely spread phenomenon in Morocco’s rapidly growing coastal suburb of Harhoura, Rabat. While previous research has already focused on the socio-economic aspects of informal adaptations in affordable and middle-class housing contexts in Morocco, it leaves a gap regarding how HI is expressed in affluent settings independently and in relation to the other contexts. This research aims to visually capture how residents adapt their housing through unauthorized modifications. The research objectives are to analyze informalities that are unique to affordable, middle-class, and affluent housing and to examine if there are any shared HI patterns that transcend socio-economic contexts. This paper utilizes a mixed-methods approach by superposing fieldwork data, including the recollection of existing buildings and authorized archival data, with the help of a referential grid based on three case studies in Harhoura, Rabat, affordable, middle-class, and affluent settings, which enables effective individual and communal spatial-morphological analyses. The findings reveal distinctive and shared patterns from one side and propagation dynamics from the other, including important concepts, such as mirroring (the replication of similar informalities) and contrast (the implementation of informalities in contrast with the existing ones), between the different socio-economic contexts, which suggest higher transcending shared needs between them. By showcasing that people of diverse socio-economic means adapt their homes in strikingly similar ways, this study discredits the assumption that poverty is the primary driver of renovation approaches. This broadened lens enriches our understanding of how urban housing evolves and points to the urgency of inclusive strategies addressing key housing priorities for all.